Physico-chemical Properties and Cooking Quality of Rice Somaclone (RSC2018-1) Developed from an Aromatic Local Landrace - Remme, R N; Parvin, S; Kabir, R; Mamun, A A; Islam, M S; Islam, M M (Journal of the Bangladesh Agricultural University, 2024)
Local rice cultivars are an important source of biotic and abiotic stress-resistant genes and require special assistance to improve their qualitative and quantitative traits. A rice somaclone RSC2018-1 was isolated from a vulnerable aromatic rice cultivar Benapole. We investigated nutritional, physical, and cooking qualities of this line and compared with its mother genotype. The experiment was laid out in Completely Randomized Design with four replications. Nutritional analysis revealed that somaclone RSC2018-1 had more protein (16.14%), less fat (0.70%) and carbohydrate (75.19%) than those of mother Benapole. Mineral components e.g. Na and Fe were higher (91.23 ppm and 20.02 ppm, respectively) in the RSC2018-1, while K and Zn contents were higher (196.67 ppm and 31.70 ppm, respectively) in mother Benapole. The size of the grain was much shorter in RSC2018-1 than in Benapole. Shape of the grain is round in RSC2018-1 while Benapole has a bold shape grain. Thousand-grain weight, geometric mean dimension, and surface area were comparatively much lesser in the somaclone line. Sphericity, aspect ratio, bulk density and porosity were higher in somaclone than in Benapole. RSC2018-1 showed a shorter cooking time (21.78 minutes), intermediate alkali digestion, intermediate gelatinization temperature, and soft gel consistency (60.78 mm) through cooking qualities analysis. Considering all physicochemical and cooking properties, the somaclone (RSC2018-1) has been found more superior in comparison with mother cultivar Ranisalute. J Bangladesh Agril Univ 22(4): 422-431, 2024